A tourist market portfolio for Portugal - Águas, P.; Costa, J.; Rita, P. (International Journal of Contemporary Hospitality Management, 2000)
The main objective of this study is the application of portfolio analysis, as an instrument of decision-making support, to the selection of priority market segments for Portugal. The results obtained validate the use of competitiveness and attractiveness as tools for the selection and management of generating markets for a tourist destination. The selection of factors to calculate the values of competitiveness and attractiveness was based on a review of the literature on destination competitiveness, portfolio models in general and studies applied to tourist destinations. The relative importance of the factors was determined after consultation with a panel of experts. Cronbach's alpha test was used to verify the scale reliability. Tourist arrivals, tourists stays, foreign exchange revenue and bednights in hotel units were used as performance indicators of generating countries. Correlation and multiple linear regression analysis were used to study the relation between attractiveness and competitiveness and performance.